Chemical composition and sensory profiles of mulberry wines as fermented with different Saccharomyces cerevisiae strains. (29th December 2017) - Tao, Yang; Wang, Yilin; Yang, Jun; Wang, Qi; Jiang, Na; Chu, Dinh-Toi; Han, Yongbin; Zhou, Jianzhong
ABSTRACT: The aim of this article was to study the influence of Saccharomyces cerevisiae strains on the chemical composition and sensory properties of mulberry wines. For this purpose, three Saccharomyces cerevisiae strains, YJM 681 (isolated from raspberry), ySR 127 (commercial yeast) and Y1 (isolated from kefir fermented milk) were used for the alcoholic fermentation of mulberry juice. Yeast strains had deep influences on oenological, phenolic, amino acid, volatile and sensory profiles of resulting mulberry wines. Specifically, the beverages fermented with YJM 681 were characterised by relatively high volatile acidity and high contents of total flavonols, amino acids and some phenolic acids, including protocatechuic acid, p -hydroxybenzoic acid, caffeic acid and veratric acid. Samples fermented with ySR 127 possessed higher cyanidin-3- O -glucoside content, whereas, total amino acid content was markedly lower than that of other samples. Furthermore, mulberry wines fermented with Y1 showed the lowest volatile acidity and the lowest contents of total anthocyanins and tartaric esters. The amounts of major aromatic compounds, including 1-propanol, 2-methyl-1-propanol and ethyl acetate inside were also smaller than that of samples fermented with YJM 681 and ySR 127. Besides, the sensory results revealed that mulberry wines fermented with Y1 exhibited the lowest intensity of fruity aroma, while samples fermented with ySR 127 had the strongest sour and sweet tastes and aftertaste. These findings provide fundamental knowledge about the influence of yeast strains on the quality of mulberry wine.